Redox Flow Batteries: Machine Learning Coupled Multi‐Scale Modeling for Redox Flow Batteries (Adv. Theory Simul. 2/2020). Issue 2 (17th February 2020) - Bao, Jie; Murugesan, Vijayakumar; Kamp, Carl Justin; Shao, Yuyan; Yan, Litao; Wang, Wei
Abstract : The framework of a model combining a deep neural network and a partial differential equation solver for redox flow batteries is introduced by Jie Bao, Wei Wang, and co‐workers in article number 1900167 . Their model establishes a critical link between the micro‐structure of a flow‐battery component and its performance at the device scale, thereby providing rationale for further operational and material optimization.